1992
DOI: 10.1200/jco.1992.10.3.433
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin: an active drug in metastatic breast cancer.

Abstract: Carboplatin is an active drug in MBC patients without previous exposure to chemotherapy. In our study, the use of an experimental drug as first-line single-agent treatment in MBC did not have a negative influence on patient survival, as the majority of the carboplatin nonresponding patients could be salvaged with a conventional therapeutic regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 12 publications
3
34
0
1
Order By: Relevance
“…In a phase II study in which carboplatin was tested at an AUC of 7 mg min ml À1 -corresponding well with the median exposure of 6.7 mg min ml À1 for target AUC 6 mg min ml À1 in our study -every 4 weeks in advanced breast cancer patients, leucopenia at the time of scheduled re-treatment was found to be of grade 3 in 6% of the patients, of grade 2 in 15% and of grade 1 in 22%; the respective value for thrombocytopenia was grade 3 in 5% of the patients (O'Brien et al, 1993). Martin et al (1992), who tested a dosage of only 400 mg m À2 , every 4 weeks, in metastatic breast cancer patients, observed only infrequent and mild leucopenia and thrombocytopenia on day 28. Overall, leucopenia of only WHO grade 1 -2 was found in 47% of the patients or 18% of the courses and thrombocytopenia in 12% of the patients or 3% of the courses, respectively.…”
Section: Discussionsupporting
confidence: 86%
“…In a phase II study in which carboplatin was tested at an AUC of 7 mg min ml À1 -corresponding well with the median exposure of 6.7 mg min ml À1 for target AUC 6 mg min ml À1 in our study -every 4 weeks in advanced breast cancer patients, leucopenia at the time of scheduled re-treatment was found to be of grade 3 in 6% of the patients, of grade 2 in 15% and of grade 1 in 22%; the respective value for thrombocytopenia was grade 3 in 5% of the patients (O'Brien et al, 1993). Martin et al (1992), who tested a dosage of only 400 mg m À2 , every 4 weeks, in metastatic breast cancer patients, observed only infrequent and mild leucopenia and thrombocytopenia on day 28. Overall, leucopenia of only WHO grade 1 -2 was found in 47% of the patients or 18% of the courses and thrombocytopenia in 12% of the patients or 3% of the courses, respectively.…”
Section: Discussionsupporting
confidence: 86%
“…However, in the phase H studies of carboplatin in advanced breast cancer published so far, activity has been demonstrated mainly in untreated patients (Kolaric and Vukas, 1991;Martin et al, 1992). Vinorelbine is a novel vinca alkaloid (Potier et al, 1989) that is attractive because of the possible lack of cross-resistance with other drugs which are active against breast cancer (Henderson, 1991) and because of its low neurotoxicity, which is presumably related to its selctive affinity for mitotic tubulin and tubulinassociated proteins (Potier et al, 1989), with relative sparing of axonal microtubuks (Fellons et al, 1989).…”
Section: Methodsmentioning
confidence: 99%
“…Carboplatin, a cisplatin analogue that is significantly less nephrotoxic and neurotoxic than cisplatin itself (O'Brien et al, 1993), has attractive features as a drug for the treatment of breast cancer because it is not associated with serious organ toxicities, apart from bone marrow suppression. Relatively few phase II studies of carboplatim in advanced breast cancer have been published; in all of them a relationship between activity and lack of previous treatment has been reported (Kolaric and Vukas, 1991;Martin et al, 1992).…”
mentioning
confidence: 99%
“…More recently in a Spanish study, Martin et al (1991) reported 14 previously treated evaluable patients given carboplatin in a dose of 400 mg m-2 repeating 4 weekly. All but one of these had previously received a doxorubicin-containing regimen, usually FAC; eight of these had only received adjuvant chemotherapy.…”
Section: Carboplatinmentioning
confidence: 99%
“…In the second part of the Spanish study mentioned above, 21 previously untreated patients were given carboplatin 400 mg m2 q 4 weekly (Martin et al, 1991). Nineteen were evaluable for response and of these one achieved a CR and five a PR giving an overall response rate of 32% (13-57%).…”
Section: Carboplatinmentioning
confidence: 99%